Representasi Identitas Budaya Musi Banyuasin pada Garap Musik Tari Puyang Putri Rinai - Gregori Rahim Yuli Riadi; Teti Darlenis; Geardena Putra Yuli Riadi (Grenek: Jurnal Seni Musik, 2026)
The Puyang Putri Rinai Dance is a performing art work inspired by the legend of Puyang Putri Rinai Munai in Sungai Lilin District, Musi Banyuasin Regency. This study aims to describe the musical composition of the Puyang Putri Rinai Dance and analyze the representation of Musi Banyuasin cultural identity contained therein. The study uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, documentation, and literature studies, then analyzed using an interactive analysis model. The results show that the musical composition is played live using Malay drums, gongs, accordions, keyboards, bass, drum pads, and darbuka. The musical structure is arranged according to the needs of choreography and dramatic flow and adapts the nuances of Gending Sriwijaya as a representation of South Sumatran Malay culture. Musi Banyuasin cultural identity is represented through the legend of Putri Rinai, a symbol of female heroism, the Dawas River, and Malay musical elements. Thus, music functions not only as dance accompaniment, but also as a medium for preserving and strengthening local cultural identity.